2014
DOI: 10.1519/jsc.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Traditional and Enforced Stopping Speed and Agility Training on Multidirectional Speed and Athletic Function

Abstract: This study investigated the effects of a traditional speed and agility training program (TSA) and an enforced stopping program emphasizing deceleration (ESSA). Twenty college-aged team sport athletes (16 males, 4 females) were allocated into the training groups. Pretesting and posttesting included: 0-10, 0-20, 0-40 m sprint intervals, change-of-direction, and acceleration test (CODAT), T-test (multidirectional speed); vertical, standing broad, lateral, and drop jumps, medicine ball throw (power); Star Excursio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 28 publications
4
78
1
Order By: Relevance
“…Nevertheless, the lack of strength measurements could be considered as a limitation of the present study. In fact, according to Lockie et al [33], strength and power required for COD and linear sprinting are similar (and fit the model proposed by Young et al [4]). Moreover, the nature of the AG and COD training exercises (i.e.…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, the lack of strength measurements could be considered as a limitation of the present study. In fact, according to Lockie et al [33], strength and power required for COD and linear sprinting are similar (and fit the model proposed by Young et al [4]). Moreover, the nature of the AG and COD training exercises (i.e.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, Jovanovic et al [34] indicated that 8 weeks of a specific COD training programme appears to be an effective way of improving power performance in young soccer players. Furthermore, Lockie et al [35] suggested that complex AG training can be used to enhance explosive muscle power and dynamic athletic performance. Moreover, and according to the meta-analysis presented by Taylor et al [36], RS sprint training can induce small to large improvements in muscular power amongst already trained players.…”
Section: Discussionmentioning
confidence: 99%
“…The vertical jump was utilized to measure lower extremity power in the vertical plane. 38 The Vertec (Swift Performance Equipment, Wacol, Australia) is a standardized device, with color coded vanes, used to measure jump height performance. First, each participant stood flatfooted to the side of the Vertec (dominant hand side toward the Vertec).…”
Section: Vertical Jumpmentioning
confidence: 99%
“…Height was recorded (cm) from the highest vane moved and the vertical jump height was calculated by subtracting the standing reach height from jump height. 38 Three trials were completed, and the best trial was used for data analysis.…”
Section: Vertical Jumpmentioning
confidence: 99%